2012
DOI: 10.1038/ejhg.2012.225
|View full text |Cite
|
Sign up to set email alerts
|

An atypical Dent’s disease phenotype caused by co-inheritance of mutations at CLCN5 and OCRL genes

Abstract: Dent's disease is an X-linked renal tubulopathy caused by mutations mainly affecting the CLCN5 gene. Defects in the OCRL gene, which is usually mutated in patients with Lowe syndrome, have been shown to lead to a Dent-like phenotype called Dent disease 2. However, about 20% of patients with Dent's disease carry no CLCN5/OCRL mutations. The disease's genetic heterogeneity is accompanied by interfamilial and intrafamilial phenotypic heterogeneity. We report on a case of Dent's disease with a very unusual phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Dent disease is genetically heterogeneous: in published cohorts about 50%-60% of patients have Dent disease 1 caused by mutations of the CLCN5 gene and about 15% have Dent disease 2 caused by mutations in the OCRL gene. One case of coinheritance of mutations in both genes has been described in a patient with a phenotype close to Lowe syndrome [Addis et al, 2013]. In our cohort of 150 distinct families, Dent disease 1 represents 61% and Dent disease 2 represents 7% of the cases; most of these cases have been previously described [Hichri et al, 2011].…”
Section: Other Forms Of Dent Diseasementioning
confidence: 65%
“…Dent disease is genetically heterogeneous: in published cohorts about 50%-60% of patients have Dent disease 1 caused by mutations of the CLCN5 gene and about 15% have Dent disease 2 caused by mutations in the OCRL gene. One case of coinheritance of mutations in both genes has been described in a patient with a phenotype close to Lowe syndrome [Addis et al, 2013]. In our cohort of 150 distinct families, Dent disease 1 represents 61% and Dent disease 2 represents 7% of the cases; most of these cases have been previously described [Hichri et al, 2011].…”
Section: Other Forms Of Dent Diseasementioning
confidence: 65%
“…In a patient with tubular proteinuria, dysmorphic features, rickets, growth delay, mild cognitive and behavioral impairment, and peripapillary optic nerve atrophy with grey papillae, the co-inheritance of a CLCN5-and OCRL-mutation was found by Addis et al [136]. The OCRL splice defect observed (c.388+3A>G) locates in the region typically affected in Dent-2 disease cases and the authors suggested, that here the phenotype resulted from synergic interaction between the two mutations.…”
Section: Unusual Findings In Association With Lowe Syndromementioning
confidence: 88%
“…An XLR example is Dent's disease (CLCN5 and OCRL). 78 Again, it is difficult to prove that one mutation/gene does not suffice to cause the disease. Another problem for AD inheritance is to evaluate whether all patients have both mutations in cis, and if so, why?…”
Section: Lesson 1: In the Digenic Inheritance Examples Found To Datementioning
confidence: 99%